Design and Characterization of Ofloxacin and Dexamethasone Ocular Inserts Using Combination of Hydrophobic and Hydrophilic Polymers - Reddy, E. Sravanthi (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The objective of this work was to develop ocular inserts of ofloxacin and dexamethasone and to evaluate their potential for controlled ocular delivery. Materials and Methods: Ofloxacin and dexamethasone were obtained as a gift sample from Indu Drugs, Pvt. Ltd., hydroxy propyl methyl cellulose (HPMC) (P55 and E15) from Pellets Pharma Ltd., HPMC K4M from NSF Pharma Pvt. Ltd., Eudragit (RL-100 and L-100) from Biogen Extracts Pvt. Ltd., polyethylene glycol and ethanol were purchased from S.D. Fine Chemicals, Mumbai, India. Ocular Inserts were prepared by solvent casting technique using polymer Eudragit (RL-100 and L-100) and HPMC (K4M, P55 and E15) at different concentration and combination. Results and Discussion: 10 formulations (F1-F10) were developed and all the formulations were subjected to evaluation for thickness, weight variation, folding endurance, pH, % moisture absorption, drug content, and in vitro release study. Infrared spectral analysis showed that there is no interaction of drug with polymer which indicates the intactness of drug in the formulation. On the basis of in vitro drug release studies, formulation F6 was found to be better than the other formulations and selected as an optimized formulation, which was further subjected to stability study. No significant change was observed in the drug content and physical features during storage at 25Â°C/60% RH and 40Â°C/75% RH for 9 months. Conclusion: In this study, an attempt was made to develop ocuserts of ofloxacin and dexamethasone combination with improved bioavailability, avoidance of repeated administration and dose reduction. From the experimental finding, it can be concluded that HPMC is a hydrophilic polymer good film forming and is a promising agent for ocular delivery. Eudragit was a satisfactory polymeric ingredient to fabricate the rate controlling membrane of the ocusert system. Incorporation of polyethylene glycol enhances the flexibility of film, achieving therapeutic levels of the drug in the formulation and also permeability of the drug through cornea. The kinetic treatment of in vitro dissolution data indicated that the optimized ocusert followed Peppas kinetics with zero-order drug release. The drug remained intact and stable in the ocuserts on storage.